Multifunctional flexible membranes from sponge-like porous carbon nanofibers with high conductivity - Yan, Jianhua (Nat Commun, 2019)
Conductive porous carbon nanofibers are promising for environmental, energy, and catalysis applications. However, increasing their porosity and conductivity simultaneously remains challenging. Here we report chemical crosslinking electrospinning, a macro–micro dual-phase separation method, to synthesize continuous porous carbon nanofibers with ultrahigh porosity of >80% and outstanding conductivity of 980 S cm(−1). With boric acid as the crosslinking agent, poly(tetrafluoroethylene) and poly(vinyl alcohol) are crosslinked together to form water-sol webs, which are then electrospun into fibrous films. After oxidation and pyrolysis, the as-spun fibers are converted into B-F-N triply doped porous carbon nanofibers with well-controlled macro–meso–micro pores and large surface areas of ~750 m(2) g(−1). The sponge-like porous carbon nanofibers with substantially reduced mass transfer resistances exhibit multifunction in terms of gas adsorption, sewage disposal, liquid storage, supercapacitors, and batteries. The reported approach allows green synthesis of high-performance porous carbon nanofibers as a new platform material for numerous applications.